Understanding the policy process: analysing welfare polcy and practice - Hudson, John; Lowe, Stuart (Jaipur, 2007)
The post-industrial, twenty first century welfare state is very different from its predecessors. The heart of the Beveridge welfare state is under severe pressure as forces such as globalisation and technological progress call into question established beliefs about what governments can and should do. This book draws on the latest and best social science to explain how and why such policy change occurs. The book focuses on the policy making process as the key to change. It uses core concepts of policy analysis, one in each chapter, to build up a fully worked explanation of policy change and to equip readers with knowledge that can be applied to any aspect of welfare policy and public and social policy more generally. Understanding the policy process: introduces the main themes of the policy analysis literature; demonstrates the centrality of the policy making process to an understanding of the operational possibilities and limits of social policy; takes account of macro-, meso- and micro-level approaches to social policy analysis; uses clear explanations of key concepts, up-to-date illustrative case studies and examples to increase students' understanding of the theory and practice of policy analysis; is comparative in approach. This highly informative text is aimed at students of applied social science courses, their teachers, and those in social policy and politics departments in particular. Students who read it will understand the policy process more clearly, not just in theory but also in practice.
Keywords: Social change